PENGARUH LOKASI, HARGA DAN KERGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MALL DINOYO CITY (Studi Kasus Pada Konsumen Mall Dinoyo City) - Rahmat Nur Riandika; Rois Arifin (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis research was aimed to investigate the influence of location, price andproduct diversity to the decision of the purchase of Mall Dinoyo City MalangConsumers The population in this research is Consumers of Mall Dinoyo CityMalang in the last month Mei-July 2017. Sample taken by using the methodaccidental sampling in order to obtain 97 of respondents who qualified in thesample .This research using the primary data and multiple regression analysismethod.The result of this research shows that the variable of location has positiveand significant effect to the decision of the purchase , the variable price haspositive and significant effect to the decision of the purchase, and variable ofproduct diversity has positive and insignificant effect to the decision of thepurchase .Simultaneously variable location, price , and product diversity havesignificant influence to the decision of the purchase .Keywords:Location, Price, Product Diversity, Decision Of The Purchase.